Preserving edible biodiversity through indigenous dairy emulsions: valorization of traditional milk systems for a resilient future - Kumar, Anand; Yadav, Muskan; Ali, Sadaqat; Dutta, Itu; T, Selva Kumar; Yadav, Vidhu; Durage, Tharindu Trishan Dapana; Alhodieb, Fahad Saad; Alsanie, Saleh A. (Frontiers in Nutrition, 2025)
Traditional dairy emulsions such as ghee, laban, reyab, and fermented camel milk are produced using locally adapted livestock breeds and unique microbial consortia, reflecting centuries of ecological adaptation. These products are increasingly positioned as functional foods that integrate traditional practices with modern nutritional needs, thereby enhancing dietary diversity and sustainability. These systems are structurally complex and nutritionally dense, containing bioactive compounds, natural emulsifiers, and probiotics. They contribute to regional food resilience and edible biodiversity through bioactive compounds, natural emulsifiers, and probiotics. This paper explores the dynamic role of these emulsions in dairy food systems, their biochemical makeup, socio-cultural relevance, and technological avenues for their valorization. Advances in nano and micro emulsion methods, ultrafiltration, and spray drying are investigated for their potential to improve bioavailability, stability, and application while maintaining traditional values. Recent research has shown that when used correctly, these technologies can preserve or even enhance their health-promoting properties, allowing them to be incorporated into modern diets and treatment formulations. However, their value must be based on ethical considerations for local producers, the preservation of microbiological and cultural variety, and a governmental framework that encourages small-scale, decentralised innovations. When treated with cultural sensitivity and scientific precision, these technological interventions for the valorisation of traditional dairy systems can increase their nutritional and functional value while conserving their essential identity. These emulsions have the potential to bridge the gap between tradition and innovation, facilitating for the development of diversified, robust, and culturally grounded nutritional practices.